2019
DOI: 10.1177/2397198319826467
|View full text |Cite
|
Sign up to set email alerts
|

Raynaud’s phenomenon

Abstract: Raynaud's phenomenon can be either primary (idiopathic) or secondary to underlying disease including systemic sclerosis. Primary Raynaud's phenomenon is very common, affecting approximately 3%-5% of the general population. Although much rarer, systemic sclerosis-related Raynaud's phenomenon can be particularly severe, progressing to digital ulceration in approximately 50% of patients. Raynaud's phenomenon can have a major impact on quality of life. This review has a focus on the systemic sclerosis-related Rayn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 93 publications
0
23
0
Order By: Relevance
“…Therefore, the optimal treatment frequency and duration is currently unknown. In current recommendations and expert reviews, TPE is not reported as a therapeutic modality (3, 16). This may be because TPE is not readily available at most centers and practitioners may be reluctant to consider it due to its invasiveness, sometimes requiring central venous access when peripheral access cannot readily be obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the optimal treatment frequency and duration is currently unknown. In current recommendations and expert reviews, TPE is not reported as a therapeutic modality (3, 16). This may be because TPE is not readily available at most centers and practitioners may be reluctant to consider it due to its invasiveness, sometimes requiring central venous access when peripheral access cannot readily be obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Raynaud's phenomenon (RP), secondary to SSc, is the most frequent vascular manifestation in SSc patients. Secondary RP, the most common presenting feature of the disease, is observed in 95% of scleroderma patients and may precede diagnosis by many years [85][86][87][88]. During RP, the skin usually turns white (ischemia), blue (deoxygenation) and then red (reperfusion) [85][86][87][88].…”
Section: Peripheral Vascular Manifestationsmentioning
confidence: 99%
“…As there is an obliterative vasculopathy of the peripheral arteries and microcirculation in SRP, it often leads to critical ischemia in scleroderma. There is often a luminal narrowing of >75% of digital arteries due to underlying intimal fibrosis and luminal occlusion caused by thrombi [85][86][87][88]. Endothelial cell injury and activation lead to vascular dysfunction and vasospasm that may quickly obstruct the already limited blood flow of the vasculopathic digital arteries [41].…”
Section: Peripheral Vascular Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation
“…SSc and IIMs are characterized by the common presence of Raynaud's phenomenon (RP). This is a recurrent spasm of the terminal microcirculation, generally caused by a thermal cold shock, in which the fingers turn white (ischemic phase), blue (cyanotic phase) and red (revascularization phase) [6]. Nailfold videocapillaroscopy (NVC) is a useful, economic and rapid tool generally used for the diagnostic assessment of RP as the primary or associated with CTDs [7].…”
Section: Introductionmentioning
confidence: 99%